Disrupting the center: a partnership approach to writing across the university - Hallman Martini, Rebecca, author; Utah State University Press, publisher (Colorado State University. Libraries, 2022)
Analyzes and critiques one particular writing center's partnership-approach to collaboration with disciplinary faculty and upper administrators across the curriculum and offers writing centers a framework for responding to disruptive innovations in higher education.--Provided by publisher.
Introduction: why a strategic partnership approach in the Writing Center -- Establishing agency: laying the groundwork for strategic partnership -- Counselors, tsunamis, and well-oiled machines: partners defining their writing (center) -- Reworking with the English Department: partnering online with a first-year writing program -- Engaging challenges: partnering as a P3 with the College of Business -- Navigating workplace realities: partnering with STEM in the College of Engineering.
Keywords: Writing centers -- Administration; Strategic alliances (Business); Educational change; English language -- Rhetoric -- Study and teaching (Higher)